Students Attitudes and Perceptions towards Intercultural Communicative Competence The Case of Third Year Students at the University of Mohamed El Bachir El Ibrahimi-BBA - Kamilia Bendrimia, Amel Sehil (My University, 2019)
Abstract Convoying the demands of life in the unremittingly changing communicative globe of nowadays calls for well -instilled skills and competences. This is proved by the rapidly growing immense literature on English language teaching and learning which principally pinpoints the significant importance of the ICC and the urgent appeal for its incorporation in the classrooms of foreign languages. Exclusively; in the view that this latter is one of the most beneficial skills that help students to enhance the use of the English language in real life situations, their engagement in interactions with other people, and most interestingly assist them to become competent communicators. Even so; it seems that Algerian students face a momentous lack of awareness and are still a way far from achieving the least deal of required qualities to acquire it. Thus; this research work aims at investigating and exploring EFL students’ attitudes and perceptions towards language learning and the ICC. To do so; an amalgamation of quantitative and qualitative approaches was adopted. Furthermore; we prepared -respectively- a stratified questionnaire and a semi-structured interview for third year EFL students and their teachers at the University of El Bachir El Ibrahimi to collect the needed data and detect the validity of the implication of the CLTA in the Algerian context. By the end of this study; it can be said that thanks to the obtained findings we were able to confirm our presuppositions on students’ lack of awareness about the ICC as well as affirming our hypothesis about the implicit use of the CLTA. Conclusively; EFL teachers are recommended to thoroughly integrate the ICC in their lessons besides deploying the CLTA explicitly for the sake of enhancing and ameliorating their students’ competences to communicate and to use the language in real life situations. Keywords: ICC, CLTA, EFL Students &Teachers, Awareness, Implicit use, Algerian Context, Thorough
Keywords: Keywords: ICC, CLTA, EFL Students &Teachers, Awareness, Implicit use, Algerian Context, Thorough Explicit Integration.